AODTU-005 Risk of high grade dysplasia and submucosal invasion in different morphological sub-types of large colorectal neoplastic lesions resected at a uk tertiary referral unit. (17th June 2017) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: Although it is recognised that the risk of invasive carcinoma in apparent benign colorectal lesions differs according to morphology, the incidence varies between studies and there is limited data from large western series to inform practice. The importance of appropriate resection techniques, including ESD, is increasingly recognised in western practice. It is therefore imperative that the risk of submucosal invasion is assessed accurately to prevent inappropriate attempts at resection. We determined the risk of submucosal invasion and high grade dysplasia (HGD) in different morphological sub-types of large colorectal lesions subjected to endoscopic resection. Method: Colorectal lesions≥2 cm were included. Lesions were assessed with magnification chromoendoscopy. Data recorded included morphological type, degree of dysplasia and presence of submucosal invasion. Results: 435 colorectal lesions≥2 cm were resected. Mean lesion size was 55.2 mm (range 20 mm–160 mm). The frequency and incidence of HGD and invasive adenocarcinoma in different morphological sub-types are shown in Table 1. The incidence of HGD (8.6%) and invasive adenocarcinoma (1.2%) was very low in LST granular homogenous lesions (LST G H). LST G MN =LST granular mixed nodular LST NG =LST non-granular ESD or hybrid ESD was used to resect 97 lesions. 53% had been subjected to previous failed attempts at resection or heavy manipulation prior to referral. Of 29 invasive adenocarcinomas, 9 were deemed to be cured by endoscopic resection (superficial submucosal invasion with no adverse prognostic features). Of the remaining 20 patients, 10 were unfit for or refused surgical resection. 10 had surgery: 2 had residual tumour in the resection specimen, 5 had none and 3 had surgery at their referring institution. Only 3 patients (0.7%) with initial benign lesions developed adenocarcinoma in subsequent recurrent lesions – all were early cancers without nodal metastases at surgical resection. Conclusion: In one of the largest European series reporting the incidence of invasive carcinoma in different morphological sub-types of colorectal neoplastic lesions, we confirm that LST granular homogeneous type lesions have a very low incidence of invasive carcinoma and that care should be taken in the choice of resection technique for other sub-types of LSTs which more frequently harbour malignancy. Accurate endoscopic assessment and classification to aid meticulous lesion selection is essential. Disclosure of Interest: None Declared